The mechanisms of calcium-catalyzed graphenization of cellulose and lignin biochars uncovered - Théotime Béguerie; Elsa Weiss-Hortala; Nathalie Lyczko; Ange Nzihou (Scientific Reports, 2023)
Abstract A recent study has shown that highly crystalline graphene-based materials can be obtained from poorly organized carbon precursors using calcium as a non-conventional catalyst. XRD and TEM analyses of calcium-impregnated cellulose and lignin biochars showed the formation of well-ordered graphenic structures (Lc > 7 nm, d002 < 0.345 nm) above 1200 °C, far below the standard graphenization temperatures (T > 2000 °C). Herein, we propose new insights on the mechanism controlling the formation of highly graphenic biochars using Ca as a catalyst. We postulate that the calcium-catalyzed graphenization occurs through the formation of a metastable calcium carbide by reaction between CaO particles and amorphous carbon between 1000 and 1200 °C. CaC2 decomposes into calcium vapor and a graphenic shell covering the CaC2 particles as confirmed by TEM analysis. The thickness and planarity of the graphenic shell increase with the CaC2 initial particle size (between 20 and 200 nm), and its growth is controlled by the diffusion of the calcium vapor through the graphene layer. A much effective graphenization was obtained for the lignin biochars compared to cellulose, with Lc > 10 nm and d002 < 0.340 nm, attributed to the insertion of sulfur in the graphenic shells, which favors their ruptures and the decomposition of CaC2 into graphene. We believe that these findings would enable the reduction of costs and environmental impact of graphene-based materials synthesis using cheap and abundant renewable feedstocks and catalysts as well.